2022
DOI: 10.3389/fgene.2021.773695
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Genes Related to Postnatal Testicular Development Based on Transcriptomic Data of Testis in Hu Sheep

Abstract: The selection of testis size can improve the reproductive capacity of livestock used for artificial insemination and has been considered as an important strategy for accelerating the breeding process. Although much work has been done to investigate the mechanisms of testis development in various species, there is little information available in regard to the differences in transcriptomic profiling of sheep testes at different developmental stages. In this work, we aimed to identify differentially expressed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Zhang et al (2019) found that the expression of lncRNA was associated with sperm motility. RNA-seq technology has been successfully applied to the investigations on fertilization and the relationship between the transcriptome of ejaculated sperm and sperm quality or fertility (Xu et al, 2021;Gòdia et al, 2020b), and it was found that transcription in sperm was associated with molecular processes such as chemoattractant-activated signal transduction and ion transport and cellular components of membranes and vesicles, and that some mRNAs and microRNAs might be critical for the early development of embryos. The abundant pools of coding and noncoding RNAs in stallion sperm were not the random remnants of spermatogenesis in testis, but were selectively retained and functional consistent RNA collections (Das et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (2019) found that the expression of lncRNA was associated with sperm motility. RNA-seq technology has been successfully applied to the investigations on fertilization and the relationship between the transcriptome of ejaculated sperm and sperm quality or fertility (Xu et al, 2021;Gòdia et al, 2020b), and it was found that transcription in sperm was associated with molecular processes such as chemoattractant-activated signal transduction and ion transport and cellular components of membranes and vesicles, and that some mRNAs and microRNAs might be critical for the early development of embryos. The abundant pools of coding and noncoding RNAs in stallion sperm were not the random remnants of spermatogenesis in testis, but were selectively retained and functional consistent RNA collections (Das et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated genes included in these terms are EEA1, CNOT4, FGD4, MBNL1, ZRANB2, REV3L, XIAP, ATP13A3, RPAP2, FOXP2, ADAMTS6 , these genes are associated with mRNA surveillance pathway [18]. A parallel study by [19] described a genome-wide comparison among ovine transcriptome derived from the M0, M3, M6, and M12 sheep testes by RNA-Sequencing. A number of key genes associated with reproduction were identified, which could be defined as candidate genes controlling testis development and spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%